Intussusception Secondary to Metastatic Bladder Leiomyosarcoma: a Case Report and Review of the Literature - Muhammed Salih Süer; İsmail Oskay Kaya; Eylem Pınar Eser (Turkish Journal of Colorectal Disease)
Intussusception, where one intestinal segment telescopes into another, is rare in adults, representing 5% of all intussusception cases and 1% of bowel obstructions. This case details a 57-year-old man with primary bladder leiomyosarcoma metastatic to the liver, presenting with severe abdominal pain, nausea, and vomiting. A computed tomography scan suggested intussusception and bowel obstruction. An emergent laparotomy revealed small intestine intussusception. The affected segment was resected, and histopathology confirmed metastatic leiomyosarcoma. The patient recovered uneventfully and was discharged. This case highlights the importance of prompt diagnosis and treatment in adults with bowel obstruction and a cancer history.